Thiamine for preventing dementia development among patients with alcohol use disorder: A nationwide population-based cohort study. Issue 3 (June 2019) - Chou, Wei-Po; Chang, Yu-Han; Lin, Hung-Chi; Chang, Yi-Hsin; Chen, Yun-Yu; Ko, Chih-Hung
Summary: Objective of study: Alcohol use disorder is one of the most important factors contributing to dementia. This study examined the protective effect of thiamine administration on the incidence of dementia among patients with alcohol use disorder in Taiwan by evaluating a nationwide database. Methods: We retrieved data for this retrospective cohort study from the Longitudinal Health Insurance Database 1995–2000. Patients receiving thiamine therapy after the diagnosis of alcohol use disorder were recruited as the thiamine therapy (TT) group, and the comparison group without TT (NTT group) included randomly assigned and age-, sex-, and index year-matched individuals with alcohol use disorder. Demographic data, comorbid medical disorders, and psychotropic medication use were evaluated and controlled. The cumulative defined daily dose (DDD) was analyzed to demonstrate the dose effect. Results: Each group had 5059 patients. The TT group had a lower crude hazard ratio (0.76; 95% confidence interval: 0.60–0.96) of dementia than the NTT group. After adjusting for demographic data, comorbidity, and psychotropic medication use, the adjusted hazard ratio was 0.54 (95% confidence interval: 0.43–0.69). The significance existed among TT subjects with cumulative DDD higher than 23. The Kaplan–Meier analysis demonstrated a lower cumulative incidence of dementia in the TT group than in the NTT group. Conclusion: The results indicated that thiamine therapy could be a protective factor for dementia development in patients with alcohol use disorder. Thiamine therapy should be a crucial part of the treatment plan and health policies to prevent dementia development or progression among patients with alcohol use disorder.